(untitled) (Huellas, 2015)
In an attempt to understand the variable migration process in the context of globalization, we turn to one of its components as a trigger: the educational system of migrant populations in situations of exclusion, social vulnerability or inclusion. These categories are useful both for the interpretation of the phenomenon and for undertaking strategies leading to the resolution of different unsettling situations. The incorporation of immigrant students is a generalized issue in the education systems of most countries, and it is the responsibility of the institutions to achieve socio-cultural integration and reach intercultural coexistence. This paper aims to analyze the mechanisms of social and cultural integration of the Bolivian people in schools of Hilario Ascasubi, a town in the South West of the Province of Buenos Aires, as part of their strategies for insertion into the host space, trying to understand, from the case study, the role that education plays in the social dynamics of the group.This work used data from interviews and surveys carried out with different actors in school settings: principals, teachers, students and parents. Results were achieved from the application of quantitative and qualitative techniques.The results of this work gave rise to a series of research topics about the role of education with regard to the transmission of values for the construction of more equitable and less vulnerable societies for immigrants.